Effect of Hydrophobicity of Fluorescent Carbon Nanoparticles on Transport in Porous Media: Column Experiments and Modeling. Issue 3 (21st March 2023) - May, Daniel F.; Hassanpour, Bahareh; Sinclair, Laura; Steenhuis, Tammo S.; Cathles, Lawrence M.
Abstract: Engineered carbon‐based nanoparticles are increasingly used for environmental, industrial, and medical purposes. Thus, understanding their interaction with and transport through materials is important. We examine the impact of nanoparticle hydrophobicity and porous medium surface area on the transport of carbon nanoparticles through sand‐packed columns under saturated and unsaturated conditions. The fluorescent carbon nanoparticles (FCNs) used in this study, synthesized from citric acid and ethanolamine, exhibit synthesis‐temperature‐dependent hydrophobicity. To quantify the impact of hydrophobicity on retention, we use FCNs synthesized at four temperatures: 190°C (FCN190), 210°C (FCN210), 230°C (FCN230), and 250°C (FCN250). Several observations are noted. First, the more hydrophobic particles (FCN230 and FCN250) attain lower outlet concentrations and mass recovery than more hydrophilic particles (FCN190 and FCN210). For instance, while 77% of the FCN190 was recovered after passing through a fine‐sand‐packed column, only 23% of the FCN250 was recovered. Second, sand surface area significantly impacts FCN recovery. A 17‐fold increase in sand surface area yields a 30% decrease in the recovery of FCN210. Third, no significant difference in the mass recovery of the FCNs was observed between the unsaturated and saturated conditions, which is attributed to the small size of the FCNs relative to the water film thickness surrounding sand grains. Fourth, the particle transport model in HYDRUS‐1D successfully simulated FCN transport, showing approximately a tenfold increase in the attachment coefficient for hydrophobic FCNs. In summary, through experiments and modeling, we show that hydrophobicity is a major factor impacting FCN transport. Key Points: The synthesis‐temperature‐dependent hydrophobicity reduces the transport of fluorescent carbon nanoparticles through sand‐packed columns A two‐kinetic sites transport model describes the transport of fluorescent carbon nanoparticles in porous media Fluorescent carbon nanoparticles are not trapped in the meniscus under unsaturated conditions at the tested moisture contents